2001
DOI: 10.1054/bjoc.2001.2182
|View full text |Cite
|
Sign up to set email alerts
|

Validating automated screening for psychological distress by means of computer touchscreens for use in routine oncology practice

Abstract: SummaryThe aim of the study was to confirm the validity of using touchscreen computers for screening for clinically significant levels of distress among cancer patients in routine oncology practice. The Hospital Anxiety and Depression Scale (HADS), EORTC Quality of Life questionnaire (QLQ-C30), Mental Health Inventory-MHI5 and a Concerns Checklist were administered via touchscreen computer to 172 chemotherapy out-patients, twice, 2-4 weeks apart. A standard psychiatric interview (Present State Examination -PSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…The use of electronic questionnaire versions (e.g. tablet PCs or touch screen computers) has proved to be feasible and useful in practice (Detmar and Aaronson, 1998;Velikova et al, 1999;Cull et al, 2001). We would suggest that unspecific psychopathology questionnaires should not be used for this purpose, but rather questionnaires that are relevant to the specific experiences of cancer patients and, therefore, are of greater clinical relevancy.…”
Section: Cancer Distress P Herschbach Et Almentioning
confidence: 99%
“…The use of electronic questionnaire versions (e.g. tablet PCs or touch screen computers) has proved to be feasible and useful in practice (Detmar and Aaronson, 1998;Velikova et al, 1999;Cull et al, 2001). We would suggest that unspecific psychopathology questionnaires should not be used for this purpose, but rather questionnaires that are relevant to the specific experiences of cancer patients and, therefore, are of greater clinical relevancy.…”
Section: Cancer Distress P Herschbach Et Almentioning
confidence: 99%
“…This study (reported fully elsewhere) found that this cutoff performed adequately (sensitivity 87% and specificity 85%) and missed few interview positive cases. We administered the HADS by either a touch-screen computer (Cull et al, 2001) or when a computer was unavailable, by pen and paper. Good reliability between these two methods of administration has been previously reported (Velikova et al, 1999).…”
Section: Identification Of Cases Of Major Depressionmentioning
confidence: 99%
“…Screening can effectively detect cases of depression among oncology outpatients (Cull et al, 2001), many of whom would otherwise have been missed (Fallowfield et al, 2001). There is, however, little information on the performance of such screening systems 'in the real world.'…”
mentioning
confidence: 99%
“…Researchers demonstrated that cancer outpatients are able to use computers to report and document their psychosocial distress, [1][2][3] quality of life, [4][5][6] and pain. [7][8][9] Computer documentation is a part of practice in some hospice settings, but the clinician serves as the primary recorder.…”
Section: Introductionmentioning
confidence: 99%